Fitzpatrick, Lisa, and Shonagh Hill, eds. Plays by Women in Ireland (1926-33): Feminist Theatres of Freedom and Resistance. London: Bloomsbury Publishing, 2022. 265 pp. ISBN 978-1-350- 23463-5 - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2022)
This anthology of five plays written during the Free State years in Ireland closely follows Irish Women Dramatists 1908-2001 edited by Eileen Kearney and Charlotte Headrick (Syracuse: Syracuse UP, 2014). Both books support the idea that, although not really visible and acknowledged until the last couple of decades, there has been a female tradition in Irish playwriting throughout the last century running parallel with the much earlier identified one of male authors. The collection under review here differs from the book by Kearney and Headrick, in which the group of seven plays spans the last century, whereas the works Fitzpatrick and Hill included, Distinguished Villa by Kate O’Brien (1926), The Woman by Margaret O’Leary (1929), Youth’s the Season ─ ? by Mary Manning (1931), Witch’s Brew by Dorothy Macardle (1931), and Bluebeard by Mary Devenport O’Neill (1933) all came to life within less than a decade. Thus they reflect on similar or intertwining problems that many individuals experienced during the period, from various angles and using idiosyncratic dramaturgies.